Price Promotions: Enablers or Obstacles for Brand-Led Innovation Adoption – A Double-Hurdle Approach - Tobias Kuntner; Thorsten Teichert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Innovative new products and a strong brand are essential assets to sustain and expand a company's competitive position in the marketplace. Separate research in the innovation and marketing field has found that marketing instruments, such as price promotions, can influence both new product diffusion and brand image. However, a holistic, brand-oriented investigation of marketing drivers' effects on new product diffusion is missing. This study aims to address this gap by investigating the effect of price promotions on new product diffusion from a brand manager's perspective. The analytic basis is a large-scale panel data set that covers four established fast-moving consumer goods categories and the innovation activities of 177 brands across four years. A double-hurdle model is applied to separately explore the effects of price promotions on consumers' decisions to try and to repurchase (i.e., adopt) a new product. The results show that prices promotions' impact depends on the stage of the diffusion process: while frequent price discounts foster new product trial, they hinder the persistent adoption of new product launches. In addition, the findings reveal that a strong brand name fulfills a supporting (risk-reducing) function at the trial stage but becomes less important for persistent adoption. This study contributes to extant literature by enhancing understanding of the linkages between innovation and brand management. Furthermore, it advances methodology by applying a double-hurdle model that accounts for the two-step process of consumers' adoption decisions. Finally, it extends current knowledge on price promotion and innovation adoption by revealing opposite effects in the two innovation stages. The findings imply that managers need to handle price promotions carefully: although discounts encourage initial product trial, they should be used sparingly in later diffusion stages.
Additional information: Part of doctoral dissertation, University of Hamburg, Submitted 10.03.2016, Examiners: Prof. Dr. Thorsten Teichert, Prof. Dr. Karen Gedenk
Keywords: 330; new product introduction; brand management; price promotion; double-hurdle model